The Development of Financial Statement Analysis Learning Media to Enhance Student Analysis Abilities - Dedy Husrizal Syah; La Ane; Taufik Hidayat; Haikal Rahman (Assets: Jurnal Akuntansi dan Pendidikan, 2020)
ABSTRACTThis study aims to develop financial report analysis learning media based on mobile learning; by testing the feasibility level of the developed learning media based on validation/assessment that carried out by the expert teams and students. The Validation of Learning Media that carried out by the Media Expert team (Lecturer) and as well as testing the student analytical abilities were tested towards 40 students accounting program of State University of Medan 2018. The data analysis method used is a descriptive analysis of the percentage. In general, the media validation results fall into the category very viable whereas the result of field trial assessment also categorized as very viable.ABSTRAKPenelitian ini bertujuan untuk mengembangkan media pembelajaran analisis laporan keuangan berbasis mobile learning; dengan menguji tingkat kelayakan media pembelajaran yang dikembangkan berdasarkan validasi/penilaian dari tim ahli dan mahasiswa serta pengujian kemampuan analisis mahasiswa. Validasi media dilakukan oleh Tim Dosen Ahli Media dan diujicobakan kepada 40 mahasiswa program studi Akuntansi Universitas Negeri Medan stambuk 2018. Teknik analisa data yang digunakan adalah teknik deskriptif presentase. Secara garis besar, hasil validasi aspek media tergolong kategori sangat layak dan hasil penilaian ujicoba lapangan juga tergolong kategori sangat layak.